Direito da pessoa idosa a mobilidade urbana no município de Parintins - Azevedo, Camila Bentes de (Brasil, 2024)
The aforementioned course conclusion work alludes to the topic of the right of elderly people to urban mobility in the municipality of Parintins-Amazonas, it is a case study that sought to identify and analyze the challenges of urban mobility for elderly people in the municipality, as well as highlight the importance of Social Service in the debate on urban policies in contemporary times. The study was based on a qualitative approach, was based on bibliographical, documentary and field research, and was anchored in the dialectical structural historical method. The subjects participating in the research were two (02) elderly people who attend an Assistance Reference Center Social network in the municipality of Parintins, with whom interviews were carried out using a semi-structured script. The results of the research indicate that access to urban mobility in Parintins is still a right little achieved by the population and constitutes a great challenge for the elderly population considering their specific needs for movement in the urban environment. The importance of the service is also highlighted social in expanding the debate on urban policies considering the issue of mobility as a fundamental right that needs to be included in the agenda of public discussions for it to be effective.